From Multi-omics To Personalized Training: The Rise of Enduromics and Resistomics - Kayvan Khoramipour; Sergio Maroto-Izquierdo; Simone Lista; Alejandro Santos-Lozano; Katsuhiko Suzuki (Sports Medicine - Open)
Abstract Because of its positive effects on the cardiovascular, metabolic and neurohormonal systems, as well as other aspects of systemic physiology, exercise is crucial to overall health. Traditional exercise physiology techniques that rely on invasive procedures have limited our understanding of the molecular changes induced by exercise. This paper distinguishes the emerging fields of “enduromics” and “resistomics” from sportomics. Enduromics and resistomics concentrate on the molecular responses to endurance and resistance training, respectively, in a variety of populations, whereas sportomics stresses the study of molecular alterations in athletes in competitive or simulated situations. These fields integrate biological systems with omics technology to provide accurate insights into the many physiological responses that occur during aerobic and anaerobic exercise. These methods make it possible to create individualized training plans that maximise health, reduce injury risk and improve adherence by identifying biomarkers and metabolic fingerprints. The revolutionary potential of enduromics and resistomics for athletic performance and public health underscores the need for more research across all demographics and training modalities.